1982
DOI: 10.2170/jjphysiol.32.279
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow to brown adipose tissue and norepinephrine-induced calorigenesis in physically trained rats.

Abstract: Cardiac output (CO) and regional blood flow to various tissue were measured by means of ƒÁ-labeled plastic microspheres (15•}3 ƒÊm) injected into the left ventricle during 30-min infusion of l-norepinephrine (NE: 4 ƒÊg/(kg•Emin)) or the same amount of saline (11 ,ƒÊl/min per animal) in rats physically trained by 2-hr swimming in water of 32 (SW-32), 36 (SW-36), and 38•Ž (SW-38) for 10-11 weeks and in control (CT) rats. Body weight and skinfold thickness were significantly less in SW-36 and SW-38 than CT rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…The training also increased the amount of UCP1 antigen in BAT compared with that of the sedentary controls. Other studies examining the effects of 6-8 weeks of swim training in rodents have reported increased blood flow to BAT (Hirata, 1982), increased mitochondrial activity (Ignacio et al, 2012), and increased type 2 deiodinase (dio2) enzymatic activity and mitochondrial respiration in BAT (Ignacio et al, 2012). Rodents that experienced other exercise modalities, including 6-8 weeks of treadmill training, showed an increase in BAT activity: for example, increased cytochrome oxidase activity (Yoshioka et al, 1989), increased oxygen consumption rates (Yoshioka et al, 1989) and upregulation of BAT-specific gene markers (Yoshioka et al, 1989;Xu et al, 2011Xu et al, , 2012.…”
Section: Exercise Increases Bat Mitochondrial Activitymentioning
confidence: 89%
“…The training also increased the amount of UCP1 antigen in BAT compared with that of the sedentary controls. Other studies examining the effects of 6-8 weeks of swim training in rodents have reported increased blood flow to BAT (Hirata, 1982), increased mitochondrial activity (Ignacio et al, 2012), and increased type 2 deiodinase (dio2) enzymatic activity and mitochondrial respiration in BAT (Ignacio et al, 2012). Rodents that experienced other exercise modalities, including 6-8 weeks of treadmill training, showed an increase in BAT activity: for example, increased cytochrome oxidase activity (Yoshioka et al, 1989), increased oxygen consumption rates (Yoshioka et al, 1989) and upregulation of BAT-specific gene markers (Yoshioka et al, 1989;Xu et al, 2011Xu et al, , 2012.…”
Section: Exercise Increases Bat Mitochondrial Activitymentioning
confidence: 89%
“…hypertrophy is encountered in animals subjected to physical exercise (Östman-Smith 1979;Hirada 1982). Thus although test animals did not move more than controls, possibly they exercised/jumped more intensively, which tended to cause increased heart weight.…”
Section: Discussionmentioning
confidence: 99%
“…2). Some studies have demonstrated increased BAT activity with exercise, [61][62][63][64][65][66] others showed no change in BAT activity, [67][68][69][70] while a third set of studies reported a decrease in BAT activity with exercise. 32,[71][72][73][74] Exercise increases BAT activity Studies in rats have demonstrated that 6-8 wks of swim training for 2-3 hours per day resulted in increased blood flow to BAT and increased responsiveness to norepinephrine stimulation.…”
Section: Exercise Effects On Brown Adipose Tissue Activitymentioning
confidence: 99%
“…32,[71][72][73][74] Exercise increases BAT activity Studies in rats have demonstrated that 6-8 wks of swim training for 2-3 hours per day resulted in increased blood flow to BAT and increased responsiveness to norepinephrine stimulation. 63,64 Another study demonstrated that 8 wks of exercise training by swimming significantly increased BAT mitochondrial activity in rats. 61 In this study, rats were subjected to an exercise training protocol where they swam in a thermoneutral (31-33 C), 1 gallon, plastic barrel for up to 75 minutes per day.…”
Section: Exercise Effects On Brown Adipose Tissue Activitymentioning
confidence: 99%